Secretory carcinoma of the breast, commonly exhibits the features of low grade, triple negative breast carcinoma- A Case report with updated review of literature - Nirmalya Banerjee; Devmalya Banerjee; Neha Choudhary (University of São Paulo, 2021)
Secretory carcinoma of the breast (SBC) is a rare breast neoplasm. Most of the patients present at an early stage with a relatively indolent clinical course. Lymph node and distant metastasis are also very infrequent. The histomorphological features of the secretory breast carcinoma are quite characteristic. Predominantly three histological patterns, solid, microcystic, and tubular, have been noted with copious amounts of intra and extracellular secretory material. Most commonly, no positivity for estrogen receptor (ER), progesterone receptor (PR) and ERBB2(HER2/neu) is observed in SBCs. As SBC can occasionally be hormone receptor-positive, they should not be categorized in the triple-negative breast carcinoma (TNBC) group in general. A very characteristic genetic translocation t (12;15) has been noted in this rare tumor, resulting in a fusion between ETV6 and NTRK3 proteins. We present a case of a 60-year-old lady who presented with right breast lump of 1-month duration and was managed by lumpectomy and sentinel lymph node dissection. Axillary dissection was not performed because the sentinel lymph node biopsy was negative. Postoperative radiotherapy was given to the right breast with a boost to the tumor bed. No adjuvant chemotherapy was given No recurrence has been noted even after a year of the completion of treatment